Family Bonds and Womb Ties and Their Contact with Reality for Shaarawy - Ahmad , Muhammad Hafez Jamil; Karim , Qais Jalil (Dirasat: Human and Social Sciences, 2023)
Objectives: This study takes extreme care about preservation of families ties which are emphasized by Qur'an in order to preserve the community because the family is the nucleus of a society. Methods: The study followed a thematic approach, where the study mentioned the Quranic verse, then proceeded with the realistic analysis of the verse, the intended meaning in this verse, and the statements of the commentators on it. Results: So, these realistic touches make the marital bonds stronger and cut off anything that makes them in conflict to achieve families’ ties. Moreover, the study found that one of the signs of faith is the connection of the womb among Muslims, and through it we can establish solidarity among the community, spreading affection and mercy. In addition to that it was found that one of the sciences that Sha'arawi has transmitted to this nation is the science of interpretation. Conclusions: Preserving family ties and maintaining kinship relationships are matters strongly encouraged by Islamic teachings. When we adhere to these principles, we strengthen the bonds between families and relatives. The legislation of laws concerning kinship ties and family bonds stems from the importance given to these aspects by Islamic teachings. The Islamic household, when fragmented, becomes susceptible to the influence of destructive ideas propagated by malevolent forces. Therefore, figures like Sheikh Al-Shaarawy paid significant attention to Quranic verses that emphasize these issues, stressing the necessity of vigilance and caution regarding their negative consequences. This is what I will elucidate in this research.